Paths Linking Maternal Resources for Care to Child Growth and Early Childhood Development in Bangladesh (P11-125-19) - Basnet, Sulochana (Curr Dev Nutr, 2019)
OBJECTIVES: The study aimed to determine the paths through which resources for care were associated with child growth and development. We hypothesized that resources could have been directly associated with child outcomes or indirectly through care behaviors. Child growth could also have mediated the association between care resources and development. METHODS: We used the baseline Alive & Thrive data from Bangladesh (n = 803 mothers and their 12–23.9-month children). Child outcomes were height-for-age z score (HAZ) and motor and language development. Care resources were maternal education, knowledge, height, body mass index (BMI), mental well-being, decision-making autonomy, employment, support in chores, and perceived support. Care included dietary diversity, cleanliness, immunization, stimulation, and adequate care. Path analyses accounting for potential confounders and clustering were used. RESULTS: Education, knowledge, health, autonomy and support were associated with child outcomes. Height (β = 0.054), BMI (β = 0.033), and mental well-being (β = 0.024) had direct associations with child HAZ. Knowledge (β = 0.0038) and perceived support (β = 0.013) were associated HAZ via immunization. Height (β = 0.034) and mental well-being (β = 0.015) were associated with motor development via HAZ. Knowledge (β = 0.0024) and perceived support (β = 0.0075) were associated with motor development via immunization and then HAZ. Autonomy (β = 0.085) and perceived support (β = -0.24) had a direct association with language. Education was associated with language via cleanliness (β = 0.011). Knowledge and perceived support had associations with language via cleanliness, and immunization and then HAZ. Height (β = 0.016), BMI (β = 0.0094), and mental well-being (β = 0.0070) were associated with language via HAZ. CONCLUSIONS: Care resources were associated with growth and development directly and via care. Child growth mediated the associations between resources and child development. Strengthening various maternal resources and integration of growth and development interventions may improve child outcomes. FUNDING SOURCES: Bill & Melinda Gates Foundation and the governments of Canada and Ireland through Alive & Thrive, managed by FHI 360, and the Patrice L. Engle Dissertation Grant in Global Early Child Development.